Water born - Ward, Rachel 1964- (Chicken House, 2014)
Nic's always loved the water, so being chosen for the swimming team means everything. When she begins to hear a disembodied voice in the pool, she turns to her dad for answers from a past he might not want to remember. And when girls her age begin mysteriously drowning, Nic may be the only one who can uncover the murky truth ...
Sequel to Drowning
Keywords: Swim teams / Fiction; Drowning victims / Fiction; Natation / Clubs / Romans, nouvelles, etc; Noyés / Romans, nouvelles, etc; Swim teams; Drowning victims; Fathers and daughters; Suspense fiction; Young adult fiction; Young adult works; Thrillers (Fiction); Fiction